Community ecology of metazoan parasites of pacific bonito Sarda chiliensis Cuvier, 1832 (Perciformes: Scombridae) from the Peruvian coast - Chero, Jhon (2016)
Metazoan parasite community of S. chiliensis of Peruvian shoreline was analyzed. Specimens of S. chiliensis (n=100) were collected from Fishing Terminal of Chorrillos, Lima, Peru between January 2013 and December 2014. Necropsies were conducted to study their metazoan parasite community. Tapeworms dominated species richness and percentage of collected individuals (N=5; 44.6%), followed by nematodes (N=4; 27.0%), acanthocephalan (N=3; 2%), flukes (N=1; 23.2%) and finally the parasitic copepods (N=1, 3%). Endoparasites dominated (97%) against ectoparasites (3%). The 21.4% of collected parasites were mature forms of metazoan gill and gastrointestinal location and 78.6% were larval forms. The three parasites with more specific importance (average prevalence and abundance) of 14 taxa were Sphyriocephalus tergestinus, Anisakis sp2 and Unitubulotestis pelamydis. The total length of S. chiliensis did not presented association between prevalence and abundance of two parasites, except for U. pelamydis that showed a relationship between the prevalence and size of the fish. The comparison between the values of kn (relative condition factor) between parasitized and non-parasitized S. chiliensis showed differences for the three parasites, having higher values in non-parasitized. The values of alpha diversity showed higher values in females than in males of S. chiliensis. Values of Chao-2 show that in the community component is required to increase the sample size because was expected to find up to 18 species (22%).